PENGARUH STRATEGI PEMBELAJARAN ACTIVE LEARNING DENGAN TEKNIK TUTOR SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 20 MEDAN - Indriyani Dhian Rachmadhani; Ardat Ardat (State Islamic University of North Sumatra, 2019)
This study was aimed to: (1) find out the use of active learning strategies with Peer Tutor techniques in VIII class SMPN 20 Medan on mathematics subjects, (2) find out the learning outcomes of students taught using active learning strategies with peer tutors in VII I class SMP 20 Medan on mathematics subjects, and (3) find out the effect of active learning strategies with peer tutoring techniques on mathematics learning outcomes of students in class VIII SMP 20 Medan. This research is quantiative research. The population is all students of VIII class SMPN 20 Medan. Sample of this study is class VIII 3 as the experimental class and class VIII 2 as the control class with 30 students in each class. The instrument is used to determine student learning outcomes is a multiple choice test in the form of a pre test and post test that has been valid. The reliability of the test is 0.828. In this study, the normality test on the pre test data on the experimental class obtained L (0,122) < L table (0,161) and control class pre test data obtained L (0.091) < L table (0,161). Whereas the normality test on the post test data on the experimental class obtained L (0,091) < L table (0,161) and the control class post test data obtained L (0,122) < L table (0,161), which means that the pre-test and post-test data in the study sample had a normal distribution. In the homogeneity test the pre test data obtained F (1,821) < F table (1,859) and post test data obtained F (1,643) < F table (1,859 ), which means the pre test data and post test on the sample used in the study is homogeneous population. From the results of the calculation of the analysis of variance sig. = 0,05, obtained t (2,030) > t table (1,672), so that Ho is rejected and Ha is accepted. The conclusion of this study explains that the mathematics learning outcomes of students who are taught with active learning learning strategies with peer tutoring techniques are better than the mathematics learning outcomes of students who are taught with conventional learning in VIII class SMP 20 Medan 2017-2018 Academic Year.